Agroforestry for Sustainable Development in Central India - Solanki, K. R.; Bisaria, A. K. (Indian Journal of Agroforestry, 2020)
Central India is the water deficit region with a sparse forest cover. As a result, farmers face acute shortage of fodder, fuel, timber and other non-timber products of trees. Being low agricultural productivity in this region, tree based farming system has considerable potential to provide a substantial sustainable income to the farmers. Major problems in promoting agroforestry are lack of awareness about the benefits, selection of tree species, non-availability of planting materials, high cost of establishment, late economic returns from the tree components, poor marketing facilities and lack of package of information for planting trees on farm lands. These problems can be resolved to the maximum extent by selecting agroforestry systems which can offer higher economic returns, promote farmers to develop their own necessary infrastructure for input supply, processing and marketing of produce. The technology and management support required to be provided by research institutes, government and non-government organizations. Financial institutions should also come forward for providing assistance to farmers to meet the cost involved in the establishment of agroforestry systems.